Operations Eclipse Sequencing in Multipurpose Dam Planning. Issue 4 (20th April 2023) - Arnold, Wyatt; Salazar, Jazmin Z.; Carlino, Angelo; Giuliani, Matteo; Castelletti, Andrea
Abstract: A resurgence of dam planning and construction is under way in river basins where untapped hydropower potential could meet growing energy demands. Despite calls for more comprehensive evaluation of dam projects, most dams continue to be planned with traditional methods that neglect interdependencies between planning and management and cumulative impacts of multiple new dams. Using the transboundary Zambezi Watercourse as a case study where competing demands for water, energy, and food are increasing, we contribute to a novel dam planning approach that integrates sequencing of planned reservoirs with adaptive operations. While additional hydropower capacity reduces structural energy deficits, operating polices emerge as the main driver of human‐environmental tradeoffs, so much so that single‐objective operating policy selection may lead to erroneous perceptions of tradeoffs across infrastructure options. Furthermore, compared to an operation and sequencing strategy that singularly maximizes hydropower, seeking compromise through operations while constructing dams early improves environmental and irrigation objectives by 50% and 80% with an 8% loss in hydropower. Alternatively, seeking compromise only through delayed dam construction yields modest environmental and irrigation improvements of 6% and 9%, respectively, with a 22% loss in hydropower. The robustness of this result is tested under an ensemble of stochastic streamflow where environmental flow and irrigation deficits are found more sensitive to operations than shifts in water availability. The predominance of operating policies is relevant for improving multi‐objective dam planning in other river basins already fragmented by dams built in the twentieth century. Key Points: A two‐part multi‐objective framework is presented that jointly optimizes the sequencing and operations of multipurpose reservoirs One or two existing reservoirs in a river basin may dominate human‐environmental tradeoffs with implications for planning new dams Reservoir operating policies eclipse reservoir network configurations and sequencing in balancing conflicting objectives